Reduction of sulfenic acids by ascorbate in proteins, connecting thiol-dependent to alternative redox pathways - Anschau, Valesca; Ferrer-Sueta, Gerardo; Aleixo-Silva, Rogerio Luis; Bannitz Fernandes, Renata; Tairum, Carlos A.; Tonoli, Celisa Caldana Costa; Murakami, Mario Tyago; de Oliveira, Marcos Antonio [UNESP]; Netto, Luis Eduardo Soares (Elsevier, 2020)
Sulfenic acids are the primary product of thiol oxidation by hydrogen peroxide and other oxidants. Several aspects of sulfenic acid formation through thiol oxidation were established recently. In contrast, the reduction of sulfenic acids is still scarcely investigated. Here, we characterized the kinetics of the reduction of sulfenic acids by ascorbate in several proteins. Initially, we described the crystal structure of our model protein (Tsa2-C170S). There are other Tsa2 structures in distinct redox states in public databases and all of them are decamers, with the peroxidatic cysteine very accessible to reductants, convenient features to investigate kinetics. We determined that the reaction between Tsa2-C170S-Cys-SOH and ascorbate proceeded with a rate constant of 1.40 ± 0.08 × 103 M−1 s−1 through a competition assay developed here, employing 2,6–dichlorophenol-indophenol (DCPIP). A series of peroxiredoxin enzymes (Prx6 sub family) were also analyzed by this competition assay and we observed that the reduction of sulfenic acids by ascorbate was in the 0.4–2.2 × 103 M−1 s−1 range. We also evaluated the same reaction on glyceraldehyde 3-phosphate dehydrogenase and papain, as the reduction of their sulfenic acids by ascorbate were reported previously. Once again, the rate constants are in the 0.4–2.2 × 103 M−1 s−1 range. We also analyzed the reduction of Tsa2-C170S-SOH by ascorbate by a second, independent method, following hydrogen peroxide reduction through a specific electrode (ISO-HPO-2, World Precision Instruments) and employing a bi-substrate, steady state approach. The kcat/KMAsc was 7.4 ± 0.07 × 103 M−1 s−1, which was in the same order of magnitude as the value obtained by the DCPIP competition assay. In conclusion, our data indicates that reduction of sulfenic acid in various proteins proceed at moderate rate and probably this reaction is more relevant in biological systems where ascorbate concentrations are high.
Keywords: Ascorbate; Peroxides; Peroxiredoxin; Sulfenic acid